Effect of cultural appropriation on the cultural garment weaving industry: the case of weavers in Addis Ababa, Ethiopia - Simret G/tsadik Araya; Berhanu Belayneh Beyene (Cogent Social Sciences, 2024)
Literature reveals that cultural appropriation (CA) involves taking over another group’s cultural belongings without consultation, informed consent and compensation, and without proper recognition or respect for that culture which has potential to distort the indigenous cultures. The purpose of this study is to examine the effect of CA on the cultural garment weaving industry in Addis Ababa, Ethiopia. The research adopted mixed methods approach with concurrent convergent research design. Data were gathered from weavers (292), consumers (200) and concerned officials by using questionnaires, KIIs (8), FGDs (3) and observation. Purposive, simple random and availability sampling method were used to determine resourceful interviewees from the weavers’ association and government agencies, respondents’ from the weaving community and consumers from the population, respectively. The study utilized descriptive and inferential statistics (Pearson correlation and multiple regression) to investigate the quantitative and narrative analysis for qualitative data. Results showed that there is CA which was driven by money making rather than respect; there is no legal and institutional framework that enable preservation, protection and commercialization of the authentic cultural designs, CA negatively impacts income and cultural identity of the owners and distorted the cultural values embedded in these designs. Thus, in order to ensure legal protection of the cultural clothes designs and rights of the weaving community, the society, weavers, weavers’ association and the responsible government authorities should work together before such sporadic wisdom and skills get vanished.